2000
DOI: 10.1111/j.1574-6968.2000.tb08923.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of electrical cable insulating oil on the mineralisation of [1-14C]glucose in soil

Abstract: Subsurface high voltage electric cables are commonly insulated using dodecylbenzene in combination with mineral oil. This work assessed the impact of increasing concentrations of cable insulating oil (0-10% dry weight) on soil microbial respiration as determined by mineralisation of [1-(14)C]glucose (11 microg C g(-1) soil). Acute impact was assessed from 0 days to 21 days, and chronic impact was assessed after 300 days. This study found that cable insulating oil increased respiratory activity of soil microflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…For each of the assessment criteria set, transformer oil was not observed to inhibit the evolution of phenanthrene catabolism, indeed the presence of oil putatively enhanced mineralisation. Application of oil to soil has been shown to result in an increase in microbial biomass since it can act as an available substrate for some groups of organisms [24], an especially important criterion in a carbon‐limited environment, such as soil [25]. Furthermore, total bacterial cell numbers and the proportion of oil‐decomposing bacteria have been shown to increase as a result of oil application [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…For each of the assessment criteria set, transformer oil was not observed to inhibit the evolution of phenanthrene catabolism, indeed the presence of oil putatively enhanced mineralisation. Application of oil to soil has been shown to result in an increase in microbial biomass since it can act as an available substrate for some groups of organisms [24], an especially important criterion in a carbon‐limited environment, such as soil [25]. Furthermore, total bacterial cell numbers and the proportion of oil‐decomposing bacteria have been shown to increase as a result of oil application [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Although not described here, another use for this respirometric system is the assessment of contaminant impact on microbial function in environmental samples. We have previously investigated contaminant impact using the mineralisation of 14 C-labelled glucose as a measure of microbial activity in soils amended with cable-insulating oil [17] and PAHs [18] in relation to microbial biomass. However, although carbon turnover tests may indicate the overall e¡ects of contaminants on the respiration of unstimulated and stimulated micro£ora, these tests give no indication of the impact on particular taxonomically different groups or species.…”
Section: Assessing Organic Contaminant Bioavailability In Soilmentioning
confidence: 99%
“…Therefore it can be argued that the uctuations within microbial communities may be due to the changes in the respiratory activity of the soil microora. 28 However, the lower extent of 14 Cphenanthrene mineralisation in the 1% amendment of CNMs and at the later stages of aging was not due to the lack of active phenanthrene-utilising microorganisms, but due to sorption effects of the CNMs. 4,12,29 It was observed that the low concentrations of C 60 had reduced CFUs, which is in agreement with the results obtained by Johansen, et al; 12 however, it is not understood how this had no effect on the extent of 14 C-phenanthrene mineralisation.…”
Section: Discussionmentioning
confidence: 92%